Stanowisko rządu brytyjskiego wobec spłaty długu wojennego Stanom Zjednoczonym (20 czerwca 1931 r. – 15 grudnia 1932 r.) - Piątek, Justyna (Acta Universitatis Lodziensis. Folia Historica, 2012)
On account of a financial collapse in Europe during the first months of 1931 and German extremely critical situation, on June 20th, 1931 President of the United States Herbert Hoover have agreed to suspend for one year (from July 1st, 1931) all international debts due to America provided that the German reparations would be postponed as well. The Hoover Moratorium seemed reasonable for British Government to hope that this was a step to lead to the end of reparations and war debts. Securing the cancellation or great reduction of those payments was the cardinal point of British policy embodied in Balfour Note of 1922. In the opinion of the British Government the Young Plan of 1929 recognized the inevitable connection between reparations and the war debts contrary to American point of view. After the Laval visit in Washington in October 1931 the debtor Powers were even more strengthened in the assumption that they could hope to obtain parallel concessions from the United States in regard to war debts in exchange for concession to Germany. Therefore it was the objective of the European Conference in Lausanne of 1932. A radical reduction of German reparations was achieved. Under the pressure of France so called gentleman’s agreement was attached which made ratification of the Lausanne Protocol dependent on a satisfactory debt settlement with the United States. The key remained in the American hands. Still Hoover and the U.S. Congress have ruled out the change of the American position toward the outstanding debt. Although the president-elect Franklin Delano Roosevelt had suggested a desire to consider the war debt question with the European debtors, nothing has changed. In view of the impossibility of carrying through discussions with America before next maturity, after the cautious considerations, in London have been decided to pay installment debt to the United States with exclusion of the payments resumption under the Funding Agreement. Nevertheless in subsequent years the debt problem remained unresolved and Lausanne Protocol was never ratified. The causes of this were mainly different points of view, lack of mutual understanding between debtors and the creditor and a contradiction between the financial and political approach.